Pengaruh Kualitas Produk, Harga Dan Promosi Terhadap Keputusan Pembelian Rumah Subsidi Pada Perumahan Salika Land (Studi Kasus PT. Salika Jaya Mandiri) - M. Ryan Faridilham; Achmad Agus Prioyono; Eris Dianawati (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study was undertaken to evaluate how Product Quality, Price, and Promotion affected Purchase Decisions at Salika Land Housing. This study employs primary data and a quantitative methodology. Technique for obtaining samples, especially nonprobability sampling with a sample size of 52 individuals. Using validity tests, reliability tests, normality tests, multiple linear regression tests, multicollinearity tests, heteroscedasticity tests, and traditional assumption tests to tackle the problem in this research. The research employed SPSS multiple linear regression analysis. The outcomes of this study include the Product Quality, Promotion, and Purchase Decision Motivation factors concurrently, with the Product Quality variable having no influence on Purchase Price Purchase Decisions and Promotion of Purchase Decisions at Salika Land Residence. Keywords : Promotion, Product Quality, Price, Purchase Decisions